THE INFLUENCE OF TEACHING METHODS AND STUDENT INTERESTS ON LEARNING MOTIVATION THROUGH STUDENT SATISFACTION AS A MEDIATING VARIABLE - Andriani Sariwardani; Ubay Rosyadi; Dade Suparna; Ratna Dewi (Cakrawala Pedagogik, 2025)
This study aims to analyze the influence of teacher teaching methods and student interest on student learning motivation, with student satisfaction as a mediating variable. Learning motivation is a crucial factor in student academic success. Innovative and interesting teacher teaching methods, as well as high student interest in the subject matter, are strongly suspected of being able to increase learning motivation. Furthermore, this study examines the role of student satisfaction with the learning process as a mechanism that connects the influence of teacher teaching methods and student interest on learning motivation. This study uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to students at Tambak Baya State Elementary School.Data analysis was carried out using path analysis techniques to test the direct and indirect effects between variables. The results of the study are expected to provide empirical insight into the importance of effective teacher teaching methods and fostering student interest in increasing learning motivation through increasing student satisfaction in the learning process. The practical implications of this study are expected to provide input for teachers and schools in designing more effective learning strategies to increase student learning motivation.